International Contributions to the System of Scholarly Communication in Iran - Erfanmanesh, Mohammadamin (Taylor & Francis, 2018)
With an increasing number of Iranian journals indexed in global citation databases such as the Web of Science (WoS), it is important to identify to what extent these journals are “internationalized” and if the international composition of these journals influences their quality. To ascertain this, a total of 38 Iranian journals covered in the Journal Citation Reports (JCR) 2013 was sampled. The internationalization of Iranian journals is considered in terms of: (a) direct contributions in terms of foreign authors’ articles published in Iran, (b) indirect contribution in terms of citations from foreign authors’ documents to articles published in Iranian journals, and (c) editorial board composition in the field drawn internationally from foreign institutions. Findings revealed that (a) foreign researchers contributed 34.8% of papers in Iranian WoS-indexed journals, (b) a total of 30.6% of citations to Iranian WoS-indexed journals were received from foreign papers or Iranian internationally collaborative papers, and (c) foreign researchers occupied 33.6% of the editorial board membership in Iranian journals. The study found that only two Iranian journals in environmental sciences and chemistry have Impact Factors (IFs) above the median of the journals in the disciplinary category areas in which they are classified in JCR (general medicine, applied mathematics, civil engineering, environmental sciences, chemistry, polymer science, agriculture, and agronomy). Additionally, eight Iranian journals have been placed in the first and second quartile (top 50%) of journals of the same field in the JCR. Results also show that some Iranian journals suffer from low international recognition depicted from foreign contributions.